1994
DOI: 10.4315/0362-028x-57.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Lactate on Toxin Production, Spore Germination and Heat Resistance of Proteolytic Clostridium botulinum Strains

Abstract: The effect of sodium lactate and sodium lactate combined with sodium chloride (NaCl) on toxin production by proteolytic strains of Clostridium botulinum was determined in peptone-yeast extract medium, pH 6.1. Both inhibitors were also tested for their effect on thermal destruction of spores. Additionally, the effect of sodium lactate on germination of spores was assessed. The inhibitory effect of sodium lactate was dependent on the applied incubation temperature. The best inhibition was obtained at low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Houtsma et al . (1994) and Juneja and Thippareddia (2004) reported that growth and toxin production by proteolytic Clostridium botulinum was inhibited by SL in a peptone–yeast extract medium (pH 6.1).…”
Section: Resultsmentioning
confidence: 99%
“…Houtsma et al . (1994) and Juneja and Thippareddia (2004) reported that growth and toxin production by proteolytic Clostridium botulinum was inhibited by SL in a peptone–yeast extract medium (pH 6.1).…”
Section: Resultsmentioning
confidence: 99%
“…However, high concentrations of l ‐lactate may inhibit germination of proteolytic Cl. botulinum (Houtsma et al. 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Concerns that sodium nitrite in meat products might result in the formation of carcinogenic N-nitrosamines and other nitrosated products led to extensive research, mainly in N. America and Europe, to try to find alternatives to sodium nitrite and sodium nitrate. Some anti-clostridial activity was identified in potassium sorbate and certain polyphosphates (Ivey et al, 1978;Sofos et al, 1979;Nelson et al, 1983), parabens (Robach and Pierson, 1978;Dymicky and Huhtanen, 1979;Reddy et al, 1982), antioxidants (Robach and Pierson, 1979;Reddy et al, 1982;Pierson and Reddy, 1982), nisin (Scott and Taylor, 1981) and sodium lactate (Maas et al, 1989;Meng and Genigeorgis, 1993;Houtsma et al, 1994) when used in combination with other conditions. Cured meat producers have minimised the risk of formation of nitrosamines by reducing the amount of nitrite used, and eliminating nitrate from most cured products.…”
Section: Effect Of Food Additivesmentioning
confidence: 99%